An innovative building envelope with variable thermal performance for passive heating systems. (1st July 2020) - Si, Pengfei; Lv, Yuexia; Rong, Xiangyang; Shi, Lijun; Yan, Jinyue; Wang, Xin
Highlights: A new building envelope with variable thermal performance under step control operation strategy was proposed; Field test results were in good agreement with model simulation results; Trade-off between solar heat gain coefficient and thermal resistance was well coordinated; Indoor thermal environment was improved with the new building envelope. Abstract: The integration of passive solar heating strategies into the existing buildings has been considered as an innovative and effective approach to mitigate energy and environmental issues. To balance the trade-off between solar heat gain and thermal insulation in traditional passive solar systems, this paper presented an innovative envelope with variable thermal performance for passive solar buildings. Field measurement was carried out to validate the feasibility of the transparent building envelope under step control operation strategy to building comfortable indoor environment especially in cold plateau areas. The experimental results show that, even under harsh climate conditions, the application of the proposed building envelope effectively increases the heat gain and maintains indoor temperature at a relatively comfortable level in the studied case. The average indoor air temperature of the studied rooms is at 13.0–14.0 °C, with the highest temperature up to 21 °C. Numerical simulation by DesignBuilder software was further developed to exploit the efficiency of the proposed building envelope under the step control operation strategy for increasing the indoor temperature. The simulation results show the same tendency with the filed measurement results. The operation strategy of opening indoor window at 10:00 am and closing at 5:00 pm can achieve the maximization of solar gain, significantly increasing the indoor temperature. Attributed to good balance between solar heat gain coefficient and thermal resistance, the average temperature of the room with the proposed envelope mode is 2.0 °C (sunny day) and 1.5 °C (cloudy day) higher than that of another three passive solar envelope operation modes, respectively. In general, the proposed building envelope with variable thermal performance has high potential to improve the indoor thermal environment in cold plateau areas at low cost.